2010
DOI: 10.3109/02699052.2010.531687
|View full text |Cite
|
Sign up to set email alerts
|

Mild traumatic brain injury and fatigue: A prospective longitudinal study

Abstract: Post-MTBI fatigue is a persistent post-concussion symptom, exacerbated by depression but not anxiety. It diminishes in the first 3 months and then becomes relatively stable, suggesting the optimum intervention placement is at 3 months or more post-MTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
97
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 68 publications
8
97
1
1
Order By: Relevance
“…Moreover, it was common for the patients' friends and family members to consider fatigue as 'laziness' or 'apathy'. In a longitudinal prospective study, Norrie et al (8) revealed that a potentially unsupportive interpretation of fatigue-related behaviors as 'laziness' or 'unwillingness' by family members or friends was reported by up to 30% of all participants. In addition, due to the continuing demands on time and excessive responsibilities of management by patients with persistent fatigue, caregivers of these patients were at increased risk of poor psychosocial outcomes (28).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, it was common for the patients' friends and family members to consider fatigue as 'laziness' or 'apathy'. In a longitudinal prospective study, Norrie et al (8) revealed that a potentially unsupportive interpretation of fatigue-related behaviors as 'laziness' or 'unwillingness' by family members or friends was reported by up to 30% of all participants. In addition, due to the continuing demands on time and excessive responsibilities of management by patients with persistent fatigue, caregivers of these patients were at increased risk of poor psychosocial outcomes (28).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the current study complete follow up data on fatigue, on which the fatigue analysis was based, was available for only 77.2% of the originally included individuals. This might have resulted in an overestimation of the actual prevalence of fatigue, as the participants who continued with the follow up were more likely to be those having fatigue (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations